Effect of COVID-19 Anthropause on Water Clarity in the Belize Coastal Lagoon - Ileana A. Callejas; Christine M. Lee; Deepak R. Mishra; Stacey L. Felgate; Claire Evans; Abel Carrias; Andria Rosado; Robert Griffin; Emil A. Cherrington; Mariam Ayad; Megha Rudresh; Benjamin P. Page; et al. (Frontiers in Marine Science, 2021)
The Coronavirus disease 2019 (COVID-19) pandemic halted human activities globally in multiple sectors including tourism. As a result, nations with heavy tourism, such as Belize, experienced improvements in water quality. Remote sensing technologies can detect impacts of “anthropauses” on coastal water quality. In this study, moderate resolution imaging spectroradiometer (MODIS) satellite data were employed along the Belizean coast to investigate impacts of the COVID-19 shutdown on water quality. The attenuation coefficient at 490 nm, K d (490), was used as an indicator of water quality, with a lower K d (490) indicating increased water clarity. Four Coastal Management Zones were characterized by marine traffic as high traffic areas (HTAs) and two as low traffic areas (LTAs). Monthly composites for two periods, 2002–2019 (baseline) and 2020 were examined for K d (490). For months prior to the COVID-19 shutdown in Belize, there was generally no significant difference in K d (490) ( p > 0.05) between 2020 and baseline period in HTAs and LTAs. Through the shutdown, K d was lower in 2020 at HTAs, but not for LTAs. At the LTAs, the K d (490)s observed in 2020 were similar to previous years through October. In November, an unusually active hurricane season in 2020 was associated with decreased water clarity along the entire coast of Belize. This study provides proof of concept that satellite-based monitoring of water quality can complement in situ data and provide evidence of significant water quality improvements due to the COVID-19 shutdown, likely due to reduced marine traffic. However, these improvements were no longer observed following an active hurricane season.